PANDANGAN ALKITAB MENGENAI PERAN ROH KUDUS DALAM PELAYANAN DAN PERTUMBUHAN GEREJA KRISTEN MASA KINI - Sinar Sinar; Febrianti Denna Saputri, Lia Tallu Padang, Zeira Milarti, Wenniarti Lius (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This study aims to analyze the Biblical perspectives on the role of the Holy Spirit in the ministry and growth of contemporary Christian churches. Through an examination of relevant Biblical texts, this research seeks to uncover key concepts regarding the Holy Spirit's role in guiding, empowering, and inspiring the church in the modern context. The research methodology involves contextual analysis of Biblical texts and the utilization of supporting theological literature sources. The study identifies the Biblical views concerning the Holy Spirit's role in empowering the ministry of present- day Christian churches. Concepts such as the bestowing of spiritual gifts, character transformation, spiritual leadership, and church restoration will be explored in depth. Additionally, the research will also explore how the Bible views the role of the Holy Spirit in maintaining church unity and guiding spiritual growth in the increasingly complex modern context. The anticipated outcomes of this research are expected to provide a clearer understanding of the Biblical perspectives regarding the role of the Holy Spirit in the ministry and growth of contemporary Christian churches. The implications of these findings could contribute to the development of ministry practices and church nurture that are grounded in Biblical teachings and guided by the Holy Spirit. Furthermore, this research may serve as a foundation for further theological reflection and discussions within the realm of practical theology and church ministry.